New labour - a survey - Wolfgang Brassloff (Wirtschaft und Gesellschaft (WuG), 2004)
Labour has won two general elections and is preparing for a third term in office. But a further victory will have to be fought for, because many people are becoming disillusioned. They give the government credit for the way it has managed the economy and acknowledge that some progress has been made in public policy. But a survey of the high-profile health, education, transport and policing services shows that much of the promised improvement has not materialised and is not even in sight. People sense that the government has run out of ideas and out of steam. Not least, after 'lraq' Tony Blair is no Ionger quite the electoral asset that he was. The invasion of lraq was always highly unpopular: furthermore many came to feel that they had been deceived. 'lraq' has also acted as a catalyst for a more general lass of trust and the government finds it difficult to achieve 'closure' and to shift attention towards its domestic agenda. Opposition is also growing from within the labour movement to government policies that are perceived to stray from Labour values and principles and that introduce 'marketisation' into the public arena. This is apparent in an increasingly critical mood in the trade union movement and in a number of parliamentary 'rebellions' by Labour backbenchers. They want to 'reclaim' the party for the traditional aspiration of reducing the large-and growing-inequalities of income and of life chances.
Keywords: 330